The Effects of Disturbance on Plant–Pollinator Interactions in the Native Forests of an Oceanic Island (Terceira, Azores) - Mário Boieiro; Mariana Ferreira; Ana Ceia-Hasse; Fabiana Esposito; Renata Santos; Gabor Pozsgai; Paulo A. V. Borges; Carla Rego (Insects)
The native biodiversity of oceanic islands is threatened by human-driven disturbance and by the growing number of species introductions which often interfere with natural ecological processes. Here, we aim to evaluate the effect of anthropogenic disturbance on plant–pollinator interactions in the native forest communities of an oceanic island (Terceira, Azores, Portugal). We found that native species predominated in preserved sites compared to disturbed ones and that the extant plant–pollinator interactions were mostly dominated by generalist species. Dipterans, particularly hoverflies, emerged as the primary flower visitors, while introduced hymenopterans (Apis mellifera and Bombus terrestris) and native beetles were locally important, respectively, in disturbed and preserved sites. Human-driven disturbance seems to be responsible for the observed differences in flower abundance and species composition between sites and to drive changes in specific network metrics (namely nestedness, interaction strength asymmetry, and specialization), particularly in one of the study areas. Our findings also suggest that native generalist species provide ecological opportunities that can facilitate the establishment of introduced species through their broad interaction networks.